ANALISIS KEBUTUHAN RUANG PARKIR PADA OBJEK WISATA PANTAI SANUR - SURYADARMAWAN, I GUSTI AGUNG GDE; WANGSA, ANAK AGUNG RATU RITAKA; LAKSMANA, IDA BAGUS GEDE ANOM SURYA (GANEC SWARA, 2024)
The parking area available at Sanur Beach currently utilizes the road body, not the special parking lot that the beach has, thus creating a significant challenge for managers and visitors. Along with the increasing popularity of Sanur Beach as a tourist destination, the road to the beach has become congested due to the number of vehicles passing by, both motorcycles and cars. This causes visitors to often park their vehicles carelessly and irregularly, which has the potential to cause safety problems and inconvenience for other road users. Many visitors park outside the beach area, thus interfering with activities on the streets around the tourist attraction, which in turn can affect the image of Sanur Beach as a friendly and organized tourist destination. This research focuses on the need for parking spaces in Sanur Beach tourist attractions, with the hope of providing an effective solution to this problem. The data used in planning the needs of parking spaces is primary data, namely the results of surveys conducted on parking managers and vehicle traffic data. The survey results show that the parking area for motorcycles is most used on Sunday afternoon, reaching almost 228 plots, while for cars, the peak of use occurs on Sunday morning, reaching 34 plots. These findings show the importance of developing better and planned parking infrastructure at Sanur Beach, to improve the visitor experience and maintain a smooth flow of traffic. Thus, careful planning in the provision of parking spaces will be a crucial step to support the sustainability of tourism at Sanur Beach.